Challenges and Benefits Teachers on The Implementation of The Curriculum Merdeka: A Systematic Literature Review - gilang manik darussalam; rohmani nur indah (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
The Merdeka Curriculum, introduced as a replacement for the 2013 Curriculum, is a recent educational framework widely adopted in Indonesia with the overarching goal of enhancing the quality of learning implementation in the country. Given that teachers play a pivotal role in any curriculum by designing learning experiences and engaging directly with students, this research aims to explore teachers' perceptions of the Merdeka Curriculum, specifically examining the challenges and benefits associated with this new educational framework in Indonesia. Employing a systematic literature review as the research method, the findings indicate that, on the whole, teachers maintain a positive outlook on the Merdeka Curriculum, recognizing its potential to elevate the quality of learning. However, when delving into teacher readiness concerning the implementation of the Merdeka Curriculum spanning areas like planning, executing learning activities, and conducting assessments it is revealed that teacher perceptions are currently deemed only sufficient. This underscores the need for additional training to enhance teachers' knowledge and skills in effectively implementing the Merdeka Curriculum.